2020
DOI: 10.2147/idr.s230335
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Phylogenetic Relatedness of <em>bla</em>N<sub>DM-1</sub> Harboring Extended-Spectrum β-Lactamase Producing Uropathogenic <em>Escherichia coli</em> and <em>Klebsiella pneumoniae</em> in the North of Iran</p>

Abstract: Background: Escherichia coli and Klebsiella pneumoniae as an important part of Enterobacterales family are important causes of both community-and hospital-acquired infections. The present study aimed to investigate the prevalence of antibiotics resistance and molecular characteristics of uropathogenic isolates of E. coli and K. pneumoniae in Iranian patients. Methods: This cross-sectional study performed on 223 Escherichia coli and 68 Klebsiella pneumoniae isolates obtained from hospitalized patients in the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
7
1
4
Order By: Relevance
“…In Iran bla NDM is mostly isolated from carbapenem-resistant Klebsiella isolates [ 54 , 55 ]; however, there have been reports of carbapenem-resistant E. coli isolates carrying this gene [ 53 , 57 58 ]. A study conducted in Ahvaz; Iran from 2014 to 2015 reported that there were no MBL-producing Enterobactericeae isolates carrying bla NDM in this region [ 59 ]. However, in 2018, this gene was found in commensal E. coli and Pseudomonas aeruginosa which indicates the dissemination of this type of resistance among bacteria in Ahvaz; Iran [ 57 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Iran bla NDM is mostly isolated from carbapenem-resistant Klebsiella isolates [ 54 , 55 ]; however, there have been reports of carbapenem-resistant E. coli isolates carrying this gene [ 53 , 57 58 ]. A study conducted in Ahvaz; Iran from 2014 to 2015 reported that there were no MBL-producing Enterobactericeae isolates carrying bla NDM in this region [ 59 ]. However, in 2018, this gene was found in commensal E. coli and Pseudomonas aeruginosa which indicates the dissemination of this type of resistance among bacteria in Ahvaz; Iran [ 57 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Iran bla NDM is mostly isolated from carbapenem-resistant Klebsiella isolates [48,49]; however, there have been reports of carbapenem-resistant E. coli isolates carrying this gene. [47,[50][51][52]. A study conducted in Ahvaz; Iran from 2014 to 2015 reported that there were no MBL-producing Enterobactericeae isolates carrying bla NDM in this region [53].…”
Section: Discussionmentioning
confidence: 99%
“…Trong đó, Klebsiella pneumoniae được biết đến là một căn nguyên gây bệnh nhiễm trùng thường gặp, nhưng lại có thể diễn biến rất nặng và tỷ lệ đề kháng kháng sinh cao [2], [4]. Chúng xâm nhập vào đường hô hấp và là một trong những nguyên nhân hàng đầu gây viêm phổi hoặc xâm nhập vào đường máu gây nhiễm trùng máu hoặc nhiễm trùng vết thương, nhiễm khuẩn đường tiết niệu... Sự kháng thuốc của Klebsiella pneumoniae cực kì nguy hiểm bởi vì bản thân loại vi khuẩn này có khả năng sinh được men β lactamase phổ rộng (ESBL: Extended Spectrum Beta-lactamase) [3], [6]. Men này làm biến đổi, phá hủy cấu trúc hóa học của kháng sinh, có khả năng phân giải hầu hết các loại kháng sinh thuộc nhóm β lactam, đặc biệt đối với penicillins và cephalosporins thế hệ thứ 3.…”
Section: đặT Vấn đềunclassified
“…Kết quả này tương đồng với một số nghiên cứu trong nước, cũng như nghiên cứu trên thế giới. Cụ thể, nghiên cứu của tác giả Chu Thị Hải Yến (2014) [4] thực hiện tại Bệnh viện Cấp cứu Trưng Vương cho tỷ lệ Klebsiella pneumoniae sinh ESBL là 30% và nghiên cứu của các tác giả Jamali S. và cs (2020) [6] tại Bắc Iran có tỷ lệ Klebsiella pneumoniae sinh enzyme ESBL là 32,4%.…”
Section: Tỷ Lệ Sinh Esbl Của Klebsiella Pneumoniaeunclassified